Succession Intention in Continuing Family Business in Indonesia during the Covid-19 Pandemic - Henry Pribadi; Sonny Agustiawan (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
The Covid-19 pandemic disrupted many industries and created a different reality of function in terms of several aspects, including family business and succession. This paper discusses how family business successor intentions regarding succeeding the family business in the near future have been affected by the pandemic. The subjects of our study are senior undergraduate business students that could potentially become successors in their family business. Our model is based on the Intention Model from the Theory of Perceived Behaviors, modified from our previous study with Intention to succeeding family business as the dependent variable. Data of 203 valid respondents was collected through quantitative survey and analyzed using a multiple linear regression model. The results of our study show that, during the pandemic, the intention of the heirs of the family business in succeeding his/her family business will be determined by the successor’s own attitude in succeeding family business, campus education, familiness, and resiliency of family business situation in facing the pandemic. https://doi.org/10.21632/irjbs.14.3.267-282